Money growth volatility and the demand for money in Germany: Friedman's volatility hypothesis revisited - Imke Brüggemann; Dieter Nautz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
Recently, the Bundesbank claimed that monetary targeting has become considerably more diffcult by the increased volatility of short-term money growth. The present paper investigates the impact of German money growth volatility on income velocity and money demand in view of Friedman's money growth volatility hypothesis. Granger-causality tests provide some evidence for a velocity-volatility linkage. However the estimation of volatility-augmented money demand functions reveals that - in contrast to Friedman's hypothesis - increased money growth volatility lowered the demand for money.
urn:nbn:de:kobv:11-10064097
Keywords: 330; ARCH models; Money growth volatility; demand for money